Pseudotrichonympha leei, Pseudotrichonympha lifesoni, and Pseudotrichonympha pearti, new species of parabasalian flagellates and the description of a rotating subcellular structure. Issue 1 (December 2017) - del Campo, Javier; James, Erick; Hirakawa, Yoshihisa; Fiorito, Rebecca; Kolisko, Martin; Irwin, Nicholas; Mathur, Varsha; Boscaro, Vittorio; Hehenberger, Elisabeth; Karnkowska, Anna; Scheffrahn, Rudolf; Keeling, Patrick
Abstract Pseudotrichonympha is a large and structurally complex genus of parabasalian protists that play a key role in the digestion of lignocellulose in the termite hindgut. Like many termite symbionts, it has a conspicuous body plan that makes genus-level identification relatively easy, but species-level diversity ofPseudotrichonympha is understudied. Molecular surveys have suggested the diversity is much greater than the current number of described species, and that many "species" described in multiple hosts are in fact different, but gene sequences from formally described species remain a rarity. Here we describe three new species fromCoptotermes andProrhinotermes hosts, including small subunit ribosomal RNA (SSU rRNA) sequences from single cells. Based on host identification by morphology and DNA barcoding, as well as the morphology and phylogenetic position of each symbiont, all three represent newPseudotrichonympha species:P. leei, P. lifesoni, andP. pearti .Pseudotrichonympha leei andP. lifesoni, both fromCoptotermes, are closely related to otherCoptotermes symbionts including the type species, P. hertwigi .Pseudotrichonympha pearti is the outlier of the trio, more distantly related toP. leei andP. lifesoni than they are to one another, and contains unique features, including an unusual rotating intracellular structure of unknown function.